Implementation of the Adiwiyata School Program in Improving Environmental Care Character at SDN 2 Senawar School Musi Banyuasin Regency - Susanti, Marlina Kiran; Widowati, Atri; Destrinelli (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
SDN 2 Senawar School Receives an Award from the South Sumatra Provincial Environmental Service as an Environmental Education Center. In addition to having general school facilities, SDN 2 Senawar also has several facilities related to environmental management efforts. Most of these school facilities are well maintained and used as learning facilities for students. The results of the researcher's observations regarding the implementation of Adiwiyata at SDN 2 Senawar are seen from 18 indicators. The researcher used a checklist sheet to see the suitability of the implementation of Adiwiyata in the field with the assessment sheet that had been made by the researcher. The results of the observation obtained a total score of 87 at the South Sumatra Province level. This value shows that the implementation of Adiwiyata at SDN 2 Senawar is classified as good. This shows that 85% of the Adiwiyata implementation indicators have been implemented well. Evidence in the field also shows that SDN 2 Senawar strongly supports efforts to improve environmental behavior among students and school residents.